An end to global warming - Williams, L. O. (Pergamon, 2002)
The 6+ billion inhabitants of earth aspire to higher standards of living. This takes energy. If fossil fuels continue to be the key source of energy their waste product, carbon dioxide, will produce disagreeable changes in the climate. Depletion of fossil fuels will cause the cost of energy and fuel based chemicals to spiral. Climate change and high fuel prices will thwart these aspirations and will increase the probability of lethal international conflicts over energy supplies. We must stop using fossil fuels. Optimistically, we could switch from fossil fuels to renewable energy sources (solar, wind, etc.). Regrettably these sources are difficult to harvest and unreliable. They cannot, alone, serve as a base load energy supply for humanity. Fission nuclear power yields extremely hazardous waste for which no fully agreeable disposal method has been developed. Laurence Williams applied aerospace systems analysis techniques to seek a new energy system. An End to Global Warming presents his results. He shows why we must stop using fossil fuels and evaluates a host of alternatives to arrive at a robust energy system that will modernize world energy production and protect the environment. A by-product of this system will ameliorate problems associated with supplying potable water and in processing waste. The nations that develop the system described in An End to Global Warming will be gifted with huge financial reward and the pride in knowing that they have preserved the earth for all mankind.